Pengolahan Limbah Industri Kerupuk Ketumbar Menggunakan Biofilter Aerobik - Dewi, Tanti Utami; Ulvi Pri Astuti; Ahmad Erlan Afiuddin; Mirna Apriani; Danang Hadi; Ferisa Jenisa (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The coriander cracker industries in Nganjuk City, commonly structured in Small Business scales are still implying conventional equipment in its production. High daily production volumes are resulting the large amounts of liquid waste containing pollutants exceeding Indonesia’s Threshold Value specifically in Chemical Oxygen Demand (COD) at 131.2 mg/L and Total Suspended Solids (TSS) at 203 mg/L. This condition causes serious environmental risks toward improper treatment. The biofilter system is one of wastewater treatment method with a simple and applicable way, applying a biological treatment approach utilizing microorganisms to reduce organic contaminants. This study aims to analyze the influence of media type on the removal efficiency of COD and TSS concentrations in coriander cracker industries’ wastewater using an aerobic biofilter system with the bioball and Kaldness K1 media. Performance testing of the aerobic biofilter demonstrated that the reactor with Kaldness K1 media achieved the highest removal efficiencies, eliminating 85.96% of COD and 95.01% of TSS by day 12. The study confirms that the Kaldnes K1 media's porous surface structure and high specific surface area enhance biofilm growth of microorganisms, thereby optimizing organic matter degradation processes.